2014
DOI: 10.1007/s10661-014-3815-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of zeolites prepared from industrial fly ash

Abstract: In this paper, we present the possibility of using fly ash to produce synthetic zeolites. The synthesis class F fly ash from the Stalowa Wola SA heat and power plant was subjected to 24 h hydrothermal reaction with sodium hydroxide. Depending on the reaction conditions, three types of synthetic zeolites were formed: Na-X (20 g fly ash, 0.5 dm3 of 3 mol · dm−3 NaOH, 75 °C), Na-P1 (20 g fly ash, 0.5 dm3 of 3 mol · dm−3 NaOH, 95 °C), and sodalite (20 g fly ash, 0.8 dm3 of 5 mol · dm−3 NaOH + 0.4 dm3 of 3 mol · dm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
144
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(176 citation statements)
references
References 39 publications
12
144
1
10
Order By: Relevance
“…Typical zeolite Na-P1 shapes, widely reported in other studies, 6,13,33,39,40 were observed in all the tests performed (Figures 2a and S1). A noteworthy feature is the morphology consisting of secondary cauliflower-like aggregates measuring approximately 10 µm ( Figure S1, tests 10 and 14).…”
Section: Zeolite Characterizationsupporting
confidence: 81%
“…Typical zeolite Na-P1 shapes, widely reported in other studies, 6,13,33,39,40 were observed in all the tests performed (Figures 2a and S1). A noteworthy feature is the morphology consisting of secondary cauliflower-like aggregates measuring approximately 10 µm ( Figure S1, tests 10 and 14).…”
Section: Zeolite Characterizationsupporting
confidence: 81%
“…It should be mentioned that the compound may have microporosity or mesoporosity; as the study by Franus et al [99], there are several ways to calculate the volume, distribution, and surface area of the pores among which are the general isotherm equation based on the combination of a modified Kelvin equation and a statistic thickness of the adsorbed film and the multilayer adsorption theory [100].…”
Section: Textural and Mechanical Characterizationmentioning
confidence: 99%
“…However, both the size of the specimens and the laboratory conditions (temperature, pressure, and percentage of aggregates) depend on the author and the results that he intends to obtain. There is a lot of research on the mechanical state of the test tubes [41,51,99,101], and it is important to mention that in most of them, the state of operation is evaluated after having been subjected to adverse media, such as chloride attack or exposure to acid media.…”
Section: Textural and Mechanical Characterizationmentioning
confidence: 99%
“…Due to the high demand of the industry for synthetic zeolites, methods for producing these materials economically are still sought. In recent years, the feasibility of using fly ashes from hard coal and brown coal has been successfully studied (Chang,Shih 1998;Hollman et al 1999;Inada et al 2005;Derkowski 2006;Fotovat et al 2009;Belviso et al 2010;Franus et al 2014) as well as ash from fluid boilers (Grela et al 2016a, Grela et al 2016b for the synthesis of zeolite materials. Owing to intense studies, it is possible to discover new zeolite structures and to obtain thorough knowledge of their properties.…”
Section: Introductionmentioning
confidence: 99%